Application Of Article 378 Of The Criminal Code Concerning Fraud In Pre-Project Selling Housing (Study at PT. GSP) - Ratih Saryani; Tami Rusli; S. Endang Prasetyawati (International Journal of Education, Vocational and Social Science, 2025)
Pre-project selling is a method of selling property before the physical development is completed or even started. In Bandar Lampung, such practices have raised public and legal concerns due to their harmful impact on consumers. A notable case involved the developer PT. GSP, reported to authorities by dozens of buyers in 2023. This study examines the application of Article 378 of the Indonesian Criminal Code (KUHP) concerning fraud in pre-project housing sales and the challenges encountered in its enforcement. Using a normative and empirical juridical approach with both primary and secondary data, the study found that applying Article 378 is legally feasible, especially when fraudulent intent can be proven from the outlet. Elements such as deception, false information, and manipulative tactics align with the legal definition of fraud. However, significant obstacles exist, including difficulties in proving men's rea (criminal intent), the absence of clear regulations governing pre-project selling, legal uncertainty, and weak inter-agency coordination among local governments, notaries, licensing offices, and law enforcement. Strengthening cooperation among these stakeholders is essential to prevent similar crimes and ensure legal protection for consumers.